CAPACITY BUILDING CIVITAS ACADEMIKA FIS UNNES (Universitas Negeri Semarang, 2018)
Along with the demands of internationalization within the Semarang State University, there needs to be a leap of movement from all elements within it such as students, lecturers and education staff. Of course, aspects of HR both in terms of quantity and quality can be seen in terms of knowledge, skills, and attitude. Based on the results of community service activities, the conclusions from this PPM activity are: Activities to increase Capacity Building for the academic community of the Faculty of Social Sciences can improve: Skills in